Shifting Paradigms: Flipped Classroom Approaches in Open and Distance Learning - M, Effendi; T, Arifin; Ardianto, Ardianto; Nurdin, Nurdin; Jamil, Jamil (Jurnal Ilmiah Iqra', 2025)
This study explores the shifting paradigms in instructional strategies by examining the application of the Flipped Classroom model within the framework of Open and Distance Learning (ODL). Utilizing a literature review method, this research analyzes scholarly articles, books, and previous studies relevant to the integration of flipped learning in virtual and remote educational settings. The data were processed through systematic reduction, organization, interpretation, and synthesis. Findings indicate that the Flipped Classroom approach significantly enhances student learning outcomes in ODL environments. By encouraging students to engage with instructional materials prior to scheduled sessions, this model transforms traditional passive learning into active participation. Students demonstrated positive responses toward the approach, citing increased preparedness and deeper understanding during synchronous interactions. The integration of video-based content and digital platforms supports a more flexible, accessible, and student-centered learning process. Furthermore, the synergy between the Flipped Classroom model and ODL enables a learning experience that is not constrained by time or space, aligning with the demands of 21st-century education. Educational experts emphasize that this paradigm shift promotes greater engagement, improved comprehension, and higher academic achievement through more interactive and efficient use of instructional time.